Analisis Pengolahan Pelaporan Eksternal RL 4A Berdasarkan Sistem Informasi Rumah Sakit Di Rumah Sakit Cirebon - Tuti Herawati; Fina Monika (MEJORA Medical Journal Awatara, 2025)
The hospital, as a healthcare service provider, must have data requirement indicators in the digital era, one of which is hospital reporting data (RL). One type, RL4a, includes morbidity and mortality data of inpatients (both living and deceased) within a one-year period. Data collection is conducted from January 1 to December 31, then recapitulated and reported through RL4a submission in the SIRS online system. This study aims to analyze the external reporting process of RL4a based on the hospital information system at Pertamina Cirebon Hospital. The research employs a quantitative descriptive method. The variables studied include RL4a external reporting, with the research objects being the SIRS online system and the instrument used being a checklist sheet. The study results indicate that the RL4a external reporting process at Pertamina Cirebon Hospital refers to the register book, disease index, coding, and the top 10 disease reports. Data processing findings show that 90% of reports comply with standards, while the remaining 10% do not. The discrepancies are due to inaccurate codification validity in relation to patient diagnoses during data entry into the SIRS, as well as the manual, one-by-one data entry method. This condition impacts work efficiency and effectiveness.